2023
DOI: 10.1108/bij-10-2022-0628
|View full text |Cite
|
Sign up to set email alerts
|

Circular economy practices in the leather products industry toward waste valorization: an approach of sustainable environmental management

Abstract: PurposeThe global resolution of embracing dynamic and intertwined production systems has made it necessary to adopt viable systems like circular economy (CE) to ensure excellency in the business. However, in emerging countries, it is challenging to implement the CE practices due to the existing problems in the supply chain network, as well as due to the vulnerable financial condition of the business after the deadly hit of COVID-19. The main aim of this research is to determine the barriers to implementing CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Such strategies may improve the readiness to overcome risk. Similarly, providing safety training to workers and maintaining safety standards (Dong et al, 2015;Maliha et al, 2023), creating awareness among management and employees (Rubel et al, 2021), preauditing and getting environmental clearance before starting a recycling operation (Chowdhury et al, 2013) and industry associations being proactive in improving social and environmental issues (Rovinaru et al, 2019) are effective in improving the readiness and capability to manage risk factors related to SRM.…”
Section: Resilience Strategies To Tackle Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such strategies may improve the readiness to overcome risk. Similarly, providing safety training to workers and maintaining safety standards (Dong et al, 2015;Maliha et al, 2023), creating awareness among management and employees (Rubel et al, 2021), preauditing and getting environmental clearance before starting a recycling operation (Chowdhury et al, 2013) and industry associations being proactive in improving social and environmental issues (Rovinaru et al, 2019) are effective in improving the readiness and capability to manage risk factors related to SRM.…”
Section: Resilience Strategies To Tackle Risk Factorsmentioning
confidence: 99%
“…gold, platinum and bronze; Grimm et al, 2014). Furthermore, mandatory sustainability reporting practices could mitigate the risks associated with SRM (Chowdhury et al, 2013;Maliha et al, 2023). SRM might also benefit from establishing integration among stakeholders (Pagoropoulos et al, 2017;Maliha et al, 2023).…”
Section: Resilience Strategies To Tackle Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…One particular study examined the circular economy using the TOPSIS method to assess waste and identified ten strategies to provide optimal solutions for organisations. Among these strategies, the integration of CE design tools was found to be the most influential (Maliha et al, 2023). Another study analysed the network of companies in the textile industry using the clustering method, focusing on the textile companies with the highest connections (Sheresheva et al, 2022).…”
Section: Casementioning
confidence: 99%
“…In addition to these examples, numerous other businesses from a range of industries are making efforts to adopt regenerative SC (RSC) practices (Banerjee & Mukhopadhyay, 2013). 3 Regenerative practices, grounded in the circular economy (CE) in SCs, can lead to cost reductions and enhanced efficiency (Maliha et al, 2023). Additionally, such practices can help to mitigate the SC risks associated with environmental disruptions, social unrest, and regulatory changes.…”
Section: Introductionmentioning
confidence: 99%